IOT based temperature and fire alarm system using Blynk in office / Muhammmad Danish Haziq Zalizam - Zalizam, Muhammmad Danish Haziq (2024)
The Internet of Things (IoT) and the Arduino microcontroller will be used in this project to construct a simple fire alarm system. To identify potential fire threats, the system uses temperature, smoke, and flame sensors. For remote management and real-time monitoring, it makes use of the Blynk platform. Through sirens, strobe lights, and voice alerts, the system offers quick and efficient alert methods. By turning on an exhaust fan and fire sprinkler system, it also incorporates automation and intelligent response. The project increases the efficiency and efficacy of fire alarm systems overall while also increasing the accuracy of fire detection, safety via real-time monitoring, and remote control. The simulation results show that IoT technology has been successfully incorporated into the fire alarm system. The system's capabilities may be increased in the future, and it might also be integrated with a centralised monitoring and administration platform. The importance of this work rests in its contribution to improving fire safety procedures, safeguarding lives, and minimising possible harm brought on by fire events. IoT, sensors, Blynk, an Arduino microcontroller, and fire alarmsystem.